Letter from Herbert Bowman to Editor of British Worker complaining about the length of the General Strike
"Letter from Herbert Bowman to Editor of British Worker complaining about the length of the General Strike" [g0732001.jpg], n.d., Bowman, Herbert TUC Organisation